Desain Foglamp Cover Mobil dengan Pendekatan Reverse Engineering: Indonesia - Tasiekh, Ilham Akbar; Riza, Rahmat; Puspaputra, Paryana (Asian Journal of Innovation and Entrepreneurship, 2024)
The car foglamp plays an important role, especially in foggy weather or when the road is covered in thick smoke. The foglamp, equipped with a cover, protects the lamp from scratches or cracks caused by dirt, gravel, or tree branches. Therefore, modifications are made to the foglamp cover to minimize these issues while also enhancing its aesthetic appeal to align with the vital function of the foglamp on four-wheeled vehicles. The method used in this study is Reverse Engineering, which includes four stages: 3D Scanning, CAD modeling, simulation analysis, and prototype creation using a 3D Printer. The simulation analysis results using CAE software show that the modified foglamp cover has better strength than the original product and a more aesthetically pleasing appearance.